The function of Anr in the differential effects of oxygen levels on biofilm development and nitrogenase performance in Pseudomonas stutzeri A1501 - Noureen Rasheed; Xize Ali; Shahab -ud-din; Irfan Khan; Arsalan Hassan; Muhammad Ali Rasheed (PLoS ONE, 2025)
Pseudomonas stutzeri A1501 exhibits a rare and notable trait: nitrogenase activity, which functions under microaerophilic conditions with limited oxygen availability. Optimal biofilm formation occurs in minimal media under nitrogen-depleted conditions. Anr is a transcription regulator with a widespread influence that accelerates the process of biofilm development. The lack of Anr adversely affects nitrogen fixation by regulating the activity of nifA, nifH, and ntrC. The anr insertion mutant significantly reduced the nitrogenase activity. Nitrogenase activity demonstrated considerable variation at different oxygen concentrations. The quantitative reverse transcription polymerase chain reaction (qRT-PCR) demonstrated a reduction in the expression of nif island genes during nitrogen fixation in the absence of anr gene. The discovery revealed that different oxygen levels in the environment significantly influence nitrogenase activity and biofilm formation. The qRT-PCR investigation demonstrated an upregulation of narL gene expression during biofilm formation, suggesting that reduced oxygen levels initiate a signaling cascade that activates the anr gene. This influences both the expression of RpoS (sigma factor) genes and the process of biofilm formation.